Differences in Student Motivation by Using Quizizz Media and Printed Books in Class VIII SMPN 27 Makassar - Rifda Nur Hikmahwati Arif; Salma Samputri; Nurfitra Yanto (ARRUS Journal of Social Sciences and Humanities, 2023)
This study aims to determine the difference in learning motivation by using Quizizz media and student books in Class VIII SMPN 27 Makassar. This type of research is Quasi-Experiment research and quantitave approach with a research design using Nonequivalent Control Group Design. The population was all students of class VIII SMPN 27 Makassar consisting of 10 classes with a total of 367 people, the sample was selected by purposive sampling, with 2 classes, namely class VIII 6 totaling 23 people as the control class and class VIII 8 totaling 23 people as the experimental class. The research instrument was a questionnaire of learning motivation and the data was analyzed with descriptive statistics and inferential statistics. The results of this study learning motivation in control and experimental classes were at a moderate level with a percentage of 39%. Inferential statistical data on learning motivation can be degrees of freedom (dk) which is 44, so that the ttable is obtained 1.68023. so that the tcount = 0.719 < ttable = 1.68023. There is no difference in the learning motivation of students using Quizizz and printed books in class VIII SMPN 27 Makassar.